Burials with Seima-Turbino Inventory from the Orenburg Сis-Urals: chronological, paleodietological and migration aspects - Lidiya V. Кuptsova; Mikhael V. Khalyapin (Археология евразийских степей, 2023)
The paper presents for the first time the materials of 4 burials from the Sintashta culture necropolis in the Orenburg Cis-Urals, where the Seima-Turbino inventory was found. The studied burials of the burial ground nearby Beryozovaya Gora were carried out according to the Seima-Turbino rite. Two of them are characterized by merging of cultural traditions. Appearance of bearers of the Seima-Turbino trasncultural phenomenon in the Orenburg Cis-Urals can be confidently associated with the migration impulse from the Western Siberia. This is evidenced by archaeological, anthropological data and the results of the analysis of light isotopes (δ¹³C and δ¹⁵N). Representatives of the Sintashta culture and bearers of the Seima-Turbino phenomenon were buried on the same burial site with the burial rite characteristics of both groups, so in this case we can talk about their peaceful coexistence. It is possible that the bearers of the Seima-Turbino phenomenon have incorporated into the Sintashta community and have kept their social status. The period of intercultural contacts, according to the radiocarbon dating of the materials from the site under discussion, falls on the XX–XVIII centuries BC. The paper also introduces for the scientific use the unpublished AMS dates of the Sintashta complexes from the Orenburg Cis-Urals.